NEWBORN NUTRITION AND ITS RELATIONSHIP TO JAUNDICE (Al-Farooq Journal of Sciences, 2026)
Background : Neonatal jaundice (NNJ) Is a Common condition affecting newborns worldwide, often influenced by feeding practices, maternal health, and familial risk factors. Understanding the interplay between newborn nutrition and the occurrence of NNJ is critical.Objective: To investigate the relationship between newborn nutrition and neonatal jaundice (physiological and pathological) and to identify maternal and familial factors associated with its incidence and duration.Methods: A cross-sectional study was conducted from January to November 2024 in two hospitals in Tripoli, Libya. A total of 200 neonates diagnosed with NNJ were included. Maternal and neonatal data, including feeding patterns, health history, and demographic characteristics, were collected using a structured questionnaire validated by experts. Reliability was confirmed using Cronbach’s alpha (0.85). Descriptive and inferential statistics were analyzed using SPSS.Results: The majority of infants (88.5%) developed jaundice within the first five days of life. Exclusive breastfeeding, mixed feeding, and bottle-feeding accounted for 37.5%, 37.5%, and 25% of infants, respectively. Maternal health conditions, including gestational diabetes (49%), hypothyroidism (42%), and high stress levels (73.5%), were significantly associated with NNJ. A positive family history of jaundice or splenectomy was reported in 39.5% and 22.5% of cases, respectively. Infants with low birth weight (1–3 kg) exhibited higher NNJ prevalence.Conclusion: Maternal health, newborn feeding practices, and family history significantly influence the development of NNJ. Early breastfeeding support, maternal health monitoring, and targeted neonatal screening are essential strategies to reduce the incidence and severity of NNJ
Keywords: Neonatal jaundice, breastfeeding, newborn nutrition, maternal health, hyperbilirubinemia